2020
DOI: 10.32479/irmm.10077
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Entrepreneurial Intention: The Prediction of Entrepreneurial Behavior

Abstract: This study examines the predictive ability of entrepreneurial behavior towards entrepreneurial intention star hotel employee in Bali. Assessing self efficacy in predicting entrepreneurial intention. Review the predictions of self-determination on entrepreneurial intention. Assessing self identity in predicting entrepreneurial intention. The Entrepreneurial behavior referred to from Kirkley (2016) research, consists of dimensions of self efficacy, self-determination, self identity. For entrepreneurial intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Similarly, it was found that perceived behavioral control and personal attitude affected entrepreneurial intention positively (Gerezgiher & Mitiku, 2018). The relationship was further reinforced by Kusumawijaya (2020a), who stated that self-efficacy can predict entrepreneurial intention significantly.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Similarly, it was found that perceived behavioral control and personal attitude affected entrepreneurial intention positively (Gerezgiher & Mitiku, 2018). The relationship was further reinforced by Kusumawijaya (2020a), who stated that self-efficacy can predict entrepreneurial intention significantly.…”
mentioning
confidence: 86%
“…A study conducted among undergraduate students in South Korea revealed that autonomy and entrepreneurial intention were related (Pérez-Macías et al, 2019). A study by Kusumawijaya (2020b) showed that autonomy could significantly influence and increase the entrepreneurial intention of star hotel employees in Bali.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, entrepreneurs need to create and venture into new fields to enhance their competitiveness by giving people more choices (Al-Mamary & Alshallaqi, 2022). Studies have recommended that entrepreneurship can be learned or by one way or another supported through entrepreneurship education (Manik & Sidharta, 2016). In addition, entrepreneurship education can likewise be considered as the proper exchange of innovative abilities and entrepreneurial competencies, that allude to the ideas, aptitudes, and mental mindfulness that people use during the time spent starting, developing and building up their development growth-oriented ventures (Shamsudin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging people to start their businesses can significantly increase effective supply, bring vitality to our economy, hasten the development of new industries, increase employment and residents’ income, and promote economic and social development ( Valliere and Peterson, 2009 ). However, enhancing people’s entrepreneurial intentions is crucial to help them build up their businesses ( Kusumawijaya, 2020 ). Considering that university students are the new force for country’s development, exploring means to enhance college students’ entrepreneurial intentions in the post-COVID-19 era is crucial for the country’s economic recovery.…”
Section: Introductionmentioning
confidence: 99%